Construction of Gold Nanoparticle-Loaded Bromelain with Potential Anti-Tumor and in vitro Wound Healing Activities - Ausaj, Amal Ahmed; Al-Shmgani, Hanady S.; Abid, Wijdan Basheer; Abada, Emad (Iraqi Journal of Science, 2026)
The most significant challenges in the advancement of cancer therapies including the adverse effects of chemotherapy, the emergence of drug resistance, and tumor metastasis, represent the major factors in therapies. In recent years, nanoparticles (NPs) have emerged as a promising paradigm in drug delivery technology. This study utilised the human breast cancer cell line MCF7 to evaluate the anticancer efficacy of gold nanoparticles (AuNPs) conjugated with bromelain (AuNPs-Br) and bromelain (Br). The AuNPs were synthesised using the Turkevich method, followed by the loading of bromelain onto these nanoparticles. Characterisation of the gold nanoparticles was conducted using various analytical techniques, including UV-Vis spectrophotometry, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). The anticancer activities were assessed through MTT cytotoxicity assays, in vitro migration assays (wound healing assays), and apoptosis detection via flow cytometry in the MCF-7 cell line and normal REF cell line. The growth inhibition of the cell line exhibited a time and dose-dependent manner. Notably, AuNPs-Br demonstrated significant cytotoxicity against MCF-7 cells, which also exhibited apoptotic events. These findings suggest potential synergistic therapeutic benefits for cancer treatment and targeted delivery strategies in human breast cancer. It's important to consider that while these findings are promising, further research and clinical evaluations are necessary to fully understand the mechanisms, effectiveness, and safety of these treatments